Investigation of Antimicrobial, Antibiofilm, and Cytotoxic Effects of Straight-Chained Sulfanyl Members of Arylamino-1,4-naphthoquinones as Potential Antimicrobial Agents - Mataracı-Kara, Emel; Jannuzzi, Ayse Tarbin; Bayrak, Nilüfer Akgün; Yıldırım, Hatice; Yıldız, Mahmut; Tuyun, Amaç Fatih; Alpertunga, Buket (Istanbul University Press, 2019)
Objective: Naphthoquinone derivatives are known to have antibacterial activity and are likely to succeed a new class of compound that can be applied as antimicrobial agents. Materials and Methods: The purpose of this experiment was to evaluate the potential antimicrobial, antibiofilm, anticancer, and cytotoxic activities of six naphthoquinone compounds previously reported in the literature. Results: According to our studies, 2-(4-(trifluoromethyl)phenylamino)-3-(propylthio)naphthalene-1,4-dione (5a) and 2-(4-(trifluoromethyl)phenylamino)-3-(pentylthio)naphthalene-1,4-dione (5b) were found to have good antimicrobial activity against Staphylococcus aureus ATCC 29213 with 1.22 and 19.53 µg/mL MIC values, respectively. When we carried out the test against biofilm, the most effective agent, 5a, showed up to 40% inhibition of the S. aureus’s biofilm at the 1 x MIC concentration. However, when we investigated the cytotoxic effect of 5a on the cancer and non-cancer cell lines, we found that 5a showed higher toxicity to cancer cell lines. Conclusion: The findings of our study suggest that further studies to develop these compounds and investigate its pharmacological properties could be useful to define the functionality of them as antimicrobial or anticancer agents. © 2023 Elsevier B.V., All rights reserved.
Keywords: 4-naphthoquinone; Antimicrobial activity; Arylamine; Biofilm; Cytotoxicity; Sulfanyl 1